Design and application of a key performance indicator (KPI) framework for autonomous shipping in Europe - Zis, Thalis; Psaraftis, Harilaos N.; Reche-Vilanova, Martina (My University, 2023)
The European Union (EU) transport policy recognizes the importance of the waterborne transport systems as key elements for sustainable growth in Europe. By 2030, 30% of total road freight over 300 km should shift to rail or waterborne transport, and more than 50% by 2050. Thus far, this ambition has failed but there have been several project initiatives within the EU to address these issues. In one of these projects, we consider a new waterborne transport system for Europe that is green, robust, flexible, more automated and autonomous, and able to connect both rural and urban terminals. The purpose of this paper is to describe work and preliminary results from this project. To that effect, and in order to assess any solutions contemplated, a comprehensive set of Key Performance Indicators (KPIs) has been defined, and three specific use cases within Europe are examined and evaluated according to these KPIs. KPIs represent the criteria under which the set of solutions developed are evaluated, and also compared to non-autonomous solutions. They are grouped under economic, environmental and social KPIs. KPIs have been selected after a consultation process involving project partners and external Advisory Group members. Links to EU transport and other regulatory action are also discussed.
Keywords: Shipping decarbonisation; Key performance indicators; Autonomous shipping; Green logistics; Maritime logistics; Autonomous terminals